Experimental investigation on compaction and Atterberg limits characteristics of soils: Aspects of clay content using artificial mixtures - Zhang, Kunyong; Frederick, Charkley Nai (KSCE Journal of Civil Engineering, 2017)
The influence of different proportions of clay minerals on the moisture density relationship and index properties of clay soils are not clearly understood because of the different factors that come into play in natural soil formation. This study used 11 different remolded samples prepared by combining double mixtures of commercially available powdered kaolinite, montmorillonite and quartz in proportions of 30%, 50%, 70% and 100% based on dry unit weight to investigate the relationship between different proportions of clay minerals with index properties and compaction characteristics of clay soils. The results described the influence of different proportions of clay minerals on the liquid limit, plastic limit and plasticity index measured using the fall cone penetration test. Also, the variation of maximum dry density and optimum moisture content with different clay mineral proportions has been analyzed. In addition, equations are presented with significant correlations to show the relationship between Atterberg limits, compaction parameters and the proportion of clay minerals. Knowledge on the effect of the different clay minerals on the moisture density relationship and index properties can be used to predict the behavior of compacted clay soils encountered in engineering practices and reduce the time and effort needed for assessing the suitability of clay soils and clay liners for engineering use.